STUDENTS’ PROBLEMS ON S-V AGREEMENT IN TOEFL AND THEIR PROPOSED SOLUTIONS - Arief Eko Priyo Atmojo (Leksema: Jurnal Bahasa dan Sastra, 2018)
This article is presented to discover the students’ problems in subject-verb (S-V) agreement and provides pedagogical solutions to these problems. This study employed descriptive design. There were two instruments used to collect data. The first instrument was a test. It consisted of 10 items with two different types of questions. The second instrument was an open-ended questionnaire consisting of two questions. The participants were 25 social science students of a private university in Yogyakarta. The data included in this study were 10 students’ works which were randomly selected. The result shows that the students' problems in S-V agreement came from their misunderstanding on: future continuous tense, singular-plural subject, appositive, the use of present participle as adjective, the use of simple present tense, the use of either … or … to show one subject, the presence of double subjects, and the use of both to show double subjects. To encounter these problems, the teacher is suggested to teach the students about the essential elements of a sentence first rather than teaching other aspects. The essential elements are subject and predicate. In short, the students must understand well that a sentence, at least, must consist of one subject and one predicate (verb). After understanding the essential elements of a sentence, the students can be taught to understand other supporting aspects which also become the causes of students’ problems in S-V agreement.